Distrust Antara Pemerintah Dengan Masyarakat Terhadap Pembangunan Hotel (Studi kasus Di Kota Yogyakarta) - Rizal, M. Hasan Syaifur (Jurnal ADMINISTRATOR, 2024)
The growth of hotels has become the most striking process in the transformation of the City of Yogyakarta based on data from the DIY Hotel Directorate in 2016. Although it seems natural like a tourist city, this phenomenon has triggered the emergence of social conflict. This study discusses the distrust between the government and the community triggered by the development of hotels in the city of Yogyakarta. This study will use the Literature Review method, which is related to the problem of collecting empirical evidence that may have been obtained using various techniques and in different research contexts. The results of this study indicate that the Yogyakarta city government is indeed playing around with capital owners, which has resulted in the public being angry and disturbed by the ease with which hotels have been built, a sign of a filter from the government. Finally, there is distrust between the public and the government regarding hotel development